Investigation on Cracks Creation and Propagation in Concrete Slab of Composite Beams - Bujnak, Jan; Furtak, Kazimierz (Communications - Scientific Letters of the University of Zilina, 2011)
Analytical and experimental research have illustrated initiation of cracks in concrete deck immediately after its casting and placing on the upper flange of steel beams, especially prior to application of additional permanent load on composite element. Not only value of concrete shrinkage strain may influence creation and propagation of cracks in concrete. However ratio of deck reinforcement, cross-sectional area of reinforcement steel and strength of concrete can modify the process. Moreover, the ratio of steel beam flexural stiffness and flexural stiffness of concrete deck can be significant. Important shrinkage strains can occur at the lower concrete surface in the steel and concrete interface. Parametrical studies have provided the relationships illustrating impact of above parameters on crack aspect. The aim of the paper is to provide further details.
Keywords: no keywords